Statins in Chronic Liver Disease: Review of the Literature and Future Role - Pham, Nguyen; Benhammou, Jihane N. (Seminars in Liver Disease, 2024)
Chronic liver disease (CLD) is a major contributor to global mortality, morbidity, and healthcare burden. Progress in pharmacotherapeutic for CLD management is lagging given its impact on the global population. While statins are indicated for the management of dyslipidemia and cardiovascular disease, their role in CLD prevention and treatment is emerging. Beyond their lipid-lowering effects, their liver-related mechanisms of action are multifactorial and include anti-inflammatory, antiproliferative, and immune-protective effects. In this review, we highlight what is known about the clinical benefits of statins in viral and nonviral etiologies of CLD and hepatocellular carcinoma (HCC), and explore key mechanisms and pathways targeted by statins. While their benefits may span the spectrum of CLD and potentially HCC treatment, their role in CLD chemoprevention is likely to have the largest impact. As emerging data suggest that genetic variants may impact their benefits, the role of statins in precision hepatology will need to be further explored.
Keywords: statin; prevention; liver disease; hepatocellular carcinoma; personalized medicine